Human resource development for effective organizations : - Lim, Ghee Soon (Cengage learning, 2013)
With the consistent governmental emphasis on training and development in the past decades, the Singapore workforce has come to view training and development as a natural part of their work and non-work lives. This learning mindset hence sets the workforce apart from those in other economies, and constitutes one of the strategic competitive advantages for the country.